Adverse health effects of PM10 particles: involvement of iron in generation of hydroxyl radical. Issue 12 (December 1996) - Gilmour, P S; Brown, D M; Lindsay, T G; Beswick, P H; MacNee, W; Donaldson, K
Abstract : OBJECTIVES: Environmental particles < 10 microns average aerodynamic diameter (PM10) are associated with mortality, exacerbation of airways diseases, and decrement in lung function. It is hypothesised that PM10 particles, along with other pathogenic particles, generate free radicals at their surface in reactions involving iron, and that this is a factor in the pathogenicity of PM10 particles. Identification of free radical activity in PM10 and examination of the content and role of iron in this process was undertaken. METHODS: Free radical activity was detected with a supercoiled plasmid, phi X174 RF1 DNA, and measured as scission of the supercoiled DNA (mediated by free radicals) by scanning laser densitometry. The role of the hydroxyl radical was confirmed by the use of the specific scavenger mannitol, and the role of iron investigated with the iron chelator desferrioxamine-B (DSF-B). Iron released from PM10 particles at pH 7.2 and pH 4.6 (to mimic conditions on the lung surface and in macrophage phagolysosomes, respectively) was assessed spectrophotometrically with the Fe++ chelator ferrozine and the Fe+ + + chelator DSF-B. RESULTS: PM10 particles showed significant free radical activity by their ability to degrade supercoiled DNA. A substantial part of this activity was due to the generation of hydroxyl radicals, as shown by partial protection with mannitol. Similarly, DSF-B also conferred protection against the damage caused to plasmid DNA indicating the role of iron in generation of hydroxyl radicals. Negligible Fe++ was released at either pH 7.2 or pH 4.6 by contrast with Fe+ + +, which was released in substantial quantities at both pHs, although twice as much was released at pH 4.6. CONCLUSIONS: PM10 particles generate the hydroxyl radical, a highly deleterious free radical, in aqueous solution. This occurs by an iron dependent process and hydroxyl radicals could play a part in the pathogenicity of PM10 particles. Iron release was greatest at the pH of the lysosome (pH 4.6) indicating that iron may be mobilised inside macrophages after phagocytosis, leading to oxidative stress in the macrophages.